Keberadaan Gender di Ranah Agama dan Budaya - Aulia Khoirunnisa (Journal of Society and Development, 2021)
In the very diverse arrangements of human life, the existence of gender is often associated with gender even though in reality gender has a broader meaning. Gender is also often seen as a boundary between men and women in doing something, behaving, or acting. Culture and religion also certainly have a great attachment to gender with the aim of creating harmony between the three things so that they become equal without discrimination and mapping even though everything must be in accordance with applicable rules and norms. The lack of harmony between gender, culture and religion can be seen from the gaps in employment, education and opinion. Although culture and religion sometimes have differences, the function of gender in both of these matters is actually the same so that gender needs to participate as a role in the development of the times with a flexible form.